Dostosowanie oferty terapii zajęciowej do potrzeb osób starszych a ich samopoczucie - Sienkiewicz-Wilowska, Julia Anastazja (Wydawnictwo Naukowe UAM, 2014)
The article presents the results of studies on the influence of matching occupational therapy offer to the needs of elderly people and the impact of this matching on their well-being. The study involved 60 people attending occupational therapy in Adult Day Care Centers in Poznan. The research was conducted with the use of the author’s Evaluation of Well-being Questionnaire, which includes 6 scales that investigate functioning in the following spheres: social, emotional, cognitive, physical, sense of personal development, and self-acceptance. Reports included standardized interviews with occupational therapists. Interviews respecting occupational therapy purposes and methods applied in this kind of elicitation. The results of this study highlight three cluster centers – cluster A (n = 5): people with malaise in all tested dimensions; cluster B (n = 15): people threatened by malaise and cluster C (n = 35): people with good well-being. Being male and a higher level of education turned out to be a risk factor. Interviews with occupational therapists confirm a poor adaptation of the activities offered to the needs of, in particular, men and the better educated.
Occupational Therapy Offer Goodness of Fit to Needs of Elderly People and Well-Being
Keywords: education of elderly people; late adulthood, occupational therapy; offer-needs goodness of fit; well-being